Chronic Immune-Mediated Orchitis Is the Major Cause of Acquired Non-obstructive Azoospermia in Dogs - Goericke-Pesch, Sandra; Reifarth, Larena; Behrens Mathiesen, Christina; Schuler, Gerhard; Umbach, Anne-Kathrin; Körber, Hanna (Frontiers in Veterinary Science, 2022)
Azoospermia, the lack of spermatozoa in the ejaculate, is the most common finding in infertile, but otherwise healthy male dogs and represents an increasing reproductive health issue in men, too. The diagnosis can be further classified as non-obstructive azoospermia (NOA) and obstructive azoospermia (OA), due to an obstruction of the deferent ducts. Although NOA comprises more than half of azoospermic cases in men and is a common cause of infertility in the male dog, knowledge of the underlying etiology and pathophysiology is still strongly limited, and much uncertainty exists about the true incidence and possible treatment options. Therefore, this study aims to investigate and characterize infertile canine patients in detail by combining results of andrological examinations (clinical parameters, semen analysis, bacterial examination of semen, Brucella canis serology), endocrine analysis (LH, testosterone, estradiol-17ß, thyroid function), analysis of the alkaline phosphatase in seminal plasma and histological assessment of testicular biopsies of 10 azoospermic dogs. Our results not only verify non-obstructive etiology for 9/10 cases of canine azoospermia, but further identified significant histopathological changes of the testicular tissue with severely disrupted spermatogenesis, including fibrotic remodelling, vacuolisation, Sertoli cell only syndrome, tubular shadows and an increase of the interstitial and vascular area. In addition, three dogs showed local, six dogs generalized immune cell infiltration, indicating chronic immune mediated orchitis. Only in one case (No.1) no immune cells were found and OA was suspected due to low alkaline phosphatase activity. Further, the detection of anti-thyroideal antibodies in two dogs indicate an autoimmune thyroid disease and a correlation between the occurrence of thyroidal disorders and azoospermia. Our results confirm previous findings and contribute additional evidence suggesting that chronic immune mediated orchitis is the major cause for infertility in dogs. Further studies should focus on uncovering underlying inflammatory processes behind spermatogenic failure in these cases and identify possible treatment options to (re-) initialize spermatogenesis.